2015
DOI: 10.1103/physreve.92.013006
|View full text |Cite
|
Sign up to set email alerts
|

Double-slit experiment with single wave-driven particles and its relation to quantum mechanics

Abstract: In a thought-provoking paper, Couder and Fort [Phys. Rev. Lett. 97, 154101 (2006)] describe a version of the famous double-slit experiment performed with droplets bouncing on a vertically vibrated fluid surface. In the experiment, an interference pattern in the single-particle statistics is found even though it is possible to determine unambiguously which slit the walking droplet passes. Here we argue, however, that the single-particle statistics in such an experiment will be fundamentally different from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 31 publications
2
67
1
Order By: Relevance
“…While claims of single-particle diffraction and interference [6] have been contested [7], tunneling [8,9], orbital quantization in both a rotating frame [10][11][12] and harmonic potential [13,14], and wavelike statistics in confined geometries [15][16][17][18] are all robust quantumlike phenomena. This hydrodynamic pilot-wave system and its relation to realist quantum theories, specifically, de Broglie's double-solution pilot-wave theory [19] and its modern extensions [20], were recently reviewed by Bush [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…While claims of single-particle diffraction and interference [6] have been contested [7], tunneling [8,9], orbital quantization in both a rotating frame [10][11][12] and harmonic potential [13,14], and wavelike statistics in confined geometries [15][16][17][18] are all robust quantumlike phenomena. This hydrodynamic pilot-wave system and its relation to realist quantum theories, specifically, de Broglie's double-solution pilot-wave theory [19] and its modern extensions [20], were recently reviewed by Bush [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] involving various degrees of sophistication in the theoretical modelling. The straight-line motion of a droplet on a free surface can be well described by an empirical ansatz which was proposed in [6], see also [7], and essentially confirmed later in [10] from a more fundamental perspective, see also [15] for a stability analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Abdurakhimov et al have recently shown an overlap between the quantum and the classical world when studying the interactions of light (electromagnetic fields) and matter (electrons) [1]. Rabi splitting of eigenfrequencies of the coupled motion is observed both in the cavity reflection spectrum and ac current of the electrons, the latter probed by measuring their bolometric photoresponse.…”
Section: Resultsmentioning
confidence: 99%
“…This was clearly demonstrated in the double slit experiment whereby light was shown to exist as both a wave and a particle, assuming either property depending on whether it is measured. As such, when observed, light will unfold as a particle and when not observed it will act as a wave function [1,5,6]. This was the basis of one the most famous debates between two of the greatest minds in the history, Einstein and Bohr [7].…”
Section: Quantum Theory Of Evolutionmentioning
confidence: 99%
See 1 more Smart Citation